Graphitized and flexible porous textile updated from waste cotton for wearable electromagnetic interference shielding. (April 2023) - Peng, Xiaoli; Meng, Xiangyu; Yu, Buyun; Chen, Hao; Liu, Zhenguo; Tang, Mingyu; Zheng, Yiqun; Sun, Yueming; Lu, Weibing; Dai, Yunqian
Abstract: Developing easy-tailorable and high-efficient electromagnetic interference (EMI) shielding textile from waste textile is highly desirable to meet the demand for wearable electronics and economic sustainability for modern society. However, simultaneously featuring with good electrical conductivity and wearability of the derived waste textiles remains a daunting challenge, especially in the absence of conducting additives. Herein, we report the fabrication of a tailorable textile with high flexibility and conductivity to address this challenge via a straightforward graphitization strategy based on a mild reduction procedure. Aided by finite element analysis (FEA) and computer simulation technology (CST) for performance screening in advance, the mechanically-favorable but EMI shielding-unfavorable pores intrinsically produced in interwoven textile call for a low square resistance of the whole textile. The textile with desirable features is fabricated by the Ni-species catalyzed graphitization of cotton cellulose with large-scale production potential. Moreover, the low square resistance of the textile remains stable after immersion in extremely corrosive chemicals or 10000-times bending tests. The textile with a small thickness of 1.4 mm achieves an EMI shielding effectiveness (SE) of 107 dB in 12–18 GHz, 3 fold exceeding the demand for commercial applications (>30 dB). Practical demonstrations show that personal information in a mobile phone or ID card can be prevented from being read by pockets tailored from textiles. This work shows great potential for massive production of high-efficiency EMI shielding textiles for livelihood or military towards the next-generation wearable electronic technology . Graphical abstract: A flexible textile of high-degree graphitization is achieved from waste cotton by employing Ni-species as the catalyst upon a mild reduction procedure. Featured with favorable conductivity and simultaneously intact interwoven framework, the textile maintains comfortable wearabilities and delivers an excellent electromagnetic shielding efficiency of 107 dB in 12–18 GHz. Image 1